(untitled) (Global Journal of Medical Research, 2014)
True umbilical cord knot is one of the abnormalities of the umbilical cord which is a rare occurrence. Constriction of a true knot of the umbilical cord may lead to obstruction of the fetal circulation and subsequent intrauterine death. We present a 20yr old primigravid,a who had a normal vaginal delivery with a true knot of the umbilical cord identified.